(untitled) (The Journal of Knowledge and Innovation, 2023)
Nursing personnel provide independent and team-based care to people of all ages, families, groups, and communities, whether ill or healthy, and in all settings. This includes promoting health, preventing illness, and providing care to the elderly, disabled, and terminally ill. Nurses play a crucial part in healthcare in hospitals and during emergencies and are frequently the unacknowledged heroes. The purpose of this study was to evaluate the factors that nursing students at Biratnagar Nursing Campus use to decide on their career path. A descriptive study design was chosen. The study was conducted at the Biratnagar Nursing Campus which is located in Morang, Nepal. A total of 89 Proficiency certificate-level (PCL) nursing students from Biratnagar Nursing Campus were considered as the study sample. The census method was used in the study. A pretested, semi-structured, self-administered questionnaire was used to collect data. Descriptive statistics was used to assess the frequency and percentage of the data. The findings of the study has shown that self-interest was one of the most important intrinsic factors influencing their decision to choose nursing as a career. Public support for the nursing profession was a significant extrinsic factor in the decision to pursue a career. The influential element in choosing nursing as a career was family recommendations.